Aspect and assertion in Mandarin Chinese - Klein, Wolfgang; Li, Ping; Hendriks, Henriëtte (Natural language & linguistic theory, 2000)
Chinese has a number of particles such as le, guo, zai and zhe that add a particular aspectual value to the verb to which they are attached. There have been many characterisations of this value in the literature. In this paper, we review several existing influential accounts of these particles, including those in Li and Thompson (1981), Smith (1991), and Mangione and Li (1993). We argue that all these characterisations are intuitively plausible, but none of them is precise.We propose that these particles serve to mark which part of the sentence's descriptive content is asserted, and that their aspectual value is a consequence of this function. We provide a simple and precise definition of the meanings of le, guo, zai and zhe in terms of the relationship between topic time and time of situation, and show the consequences of their interaction with different verb expressions within thisnew framework of interpretation.